Publisher Correction: Room temperature CO2 reduction to solid carbon species on liquid metals featuring atomically thin ceria interfaces - Dorna Esrafilzadeh (Nature Portfolio, 2019)
The original version of this Article contained errors in the author affiliations. Affiliation 1 incorrectly read ‘School of Chemical Engineering, University of New South Wales (UNSW), Sydney, NSW 2031, Australia’ and affiliation 4 incorrectly read ‘School of Engineering, RMIT University, Melbourne, VIC 3001, Australia.’ This has now been corrected in both the PDF and HTML versions of the Article.